2021
DOI: 10.14715/cmb/2021.67.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Desulfovibrio fairfieldensis adhesion on implantable titanium used in odontology: a preliminary study

Abstract: The study presented here aimed to assess the ability of Desulfovibrio fairfieldensis bacteria to adhere to and form biofilm on the structure of titanium used in implants. D. fairfieldensis was found in the periodontal pockets in the oral environment, indicating that these bacteria can colonize the implant-bone interface and consequently cause bone infection and implant corrosion. Plates of implantable titanium, of which surfaces were characterized by scanning electronic microscopy and Raman spectroscopy, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Desulfovibrio species are gram-negative bacteria that use sulfate compounds as terminal electron acceptors in their respiratory chain ( Tchinda et al., 2021 ). In humans, Desulfovibrio species ( D. fairfieldensis , D. piger , and D. vulgaris ) have been found in the oral cavity and reportedly cause infection ( Tee et al., 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Desulfovibrio species are gram-negative bacteria that use sulfate compounds as terminal electron acceptors in their respiratory chain ( Tchinda et al., 2021 ). In humans, Desulfovibrio species ( D. fairfieldensis , D. piger , and D. vulgaris ) have been found in the oral cavity and reportedly cause infection ( Tee et al., 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…As immune cells, especially macrophages and dendritic cells—the first and the main effectors of immune system—are involved in osseointegration failure of implants [ 23 ], our main objective was to analyze the grown potential of THP-1 cells expected more sensitive to metal leakage in presence of a wide range of niobate ion doses (KNbO 3 salt): 3.1 to 200 μg/mL. Indeed, released niobium species may induce local inflammation, attract bacteria and, finally, induce biofilm formation onto TiNb implants, as was evidenced with TiCp [ 45 ]. Finally, osteolysis may occur that leads to dental peri-implantitis, the main cause of implant failure.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of peri-implantitis in a group of Moroccan patients (642 implants in 145 subjects followed up for a mean of 6.4 years) was 41.4% at the subject level and 22.7% at the implant level [5]. A study conducted by Tchinda et al in 2021 suggested that anaerobic bacteria of the genus Desulfovibrio fairfieldensis can create biofilm colonies on titanium coupons and proliferate in vitro under oral physiological conditions [6]. Moreover, a few cases of titanium allergies involving dental implants are reported in the literature [7].…”
Section: Introductionmentioning
confidence: 99%